"A Good Habit": Telehealth PrEP Users Find Benefit in Quarterly Monitoring Requirements. (22nd April 2020) - Koester, Kimberly A.; Hughes, Shana D.; Grant, Robert M.
In the United States, uptake of daily oral pre-exposure prophylaxis (PrEP) to prevent HIV continues to grow albeit at a slower than desired pace. Innovations in PrEP delivery systems may partially address structural challenges related to PrEP uptake and PrEP persistence, such as difficulty in attending clinic visits or completing laboratory testing. To study PrEP services offered by a telehealth company called Nurx, we conducted 31 in-depth interviews with prospective or current patients. We hypothesized that patients would find the quarterly laboratory monitoring requirements to be onerous especially in light of receiving all other aspects of PrEP care through a telehealth delivery system. However, interviewees characterized navigating laboratory systems as relatively easy and complying with the quarterly monitoring as a supplementary benefit of PrEP use. Our research illustrates that quarterly monitoring requirements are meaningful to some telehealth PrEP users and may facilitate persistent engagement in receipt of PrEP care.